Предмет: Алгебра,
автор: IPITIN
Ответьте пожалуйста!!!!
Даю 16 баллов!!
Приложения:
Ответы
Автор ответа:
0
ответ будет : 2
6а-3у
6а-3у
Автор ответа:
0
2;3
Потому что -3(-2а+y)=6a-3y
А в свою очередь 6a-3y=3(2a-y)
Значит -3(-2a+y)=6a-3y=3(2a-y)
Ответ: 2;3
Потому что -3(-2а+y)=6a-3y
А в свою очередь 6a-3y=3(2a-y)
Значит -3(-2a+y)=6a-3y=3(2a-y)
Ответ: 2;3
Похожие вопросы
Предмет: Информатика,
автор: kamrangaraev44
Предмет: Английский язык,
автор: liana6258
Предмет: Биология,
автор: ofla
Предмет: Математика,
автор: anya140798
Предмет: Алгебра,
автор: Mimino184736